The organization of questions with focus on Biodiversity in the National High School Exam: 10 years of analysis (Research, Society and Development, 2021)
Biodiversity is important for its ecosystem services, such as water supply, air, among others. Due to its importance, it is essential to investigate possible factors that influence its teaching, such as the National High School Exam, which has a strong influence on High School. In this study, we analyzed the questions of Biology, in the Natural Sciences exam, with knowledge related to biodiversity, from the National High School Exam, between 2009 and 2018, based on the structure, frequency, and distribution. To this end, a qualitative research approach was used, based on content analysis. The results indicated three findings that impose some reflections and concerns. The first is the fact that only one question of Biology, in 10 years, has the outline of multiple answers and none of them were of the assertion-reason type, a format indicated for the assessment of more elaborate and complex cognitive processes. The second showed that some questions did not follow the problem-solving model and had characteristics more associated with a type of question in which the simple memorization of information allowed the student to solve it. The third revealed a certain imbalance in the relationship between the topic and other areas of knowledge, a situation that could affect the teaching of biodiversity in high school, which is strongly influenced by the exam. Data from this survey can help in debates about the organization of biodiversity knowledge in the largest national exam.